A Critical Review on Education in the Era of ASEAN Economic Community and Industrial Revolution 4.0: Challenges and Opportunities (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2022)
This paper aims to examine the opportunities and challenges of education in the Industrial Revolution (IR) 4.0 era in Indonesia. The presence of the ASEAN Economic Community (AEC) in the IR 4.0 era has provided great challenges and opportunities for the Indonesian people, especially in the education sphere. The technological advances in this era have had an impact on the emergence of distance learning and the use of E-Learning (electronic-based learning), which is one form of convenience in learning. It has become imperative for educators to be able to use ICT in learning. However, the negative impacts are changes in values, norms, rules, or moral life, which are contrary to those adopted by the Indonesian nation. These basic values of the nation are expected not to be eroded by the progress of the era. Therefore, the role of education as a place to shape the personality and the nation becomes very urgent.